Copper nanoparticles on controlled pore glass (CPG) as highly efficient heterogeneous catalysts for “click reactions” - Rafi, Abdolrahim A. (Sci Rep, 2020)
We herein report that supported copper nanoparticles (CuNPs) on commercially available controlled pore glass (CPG), which exhibit high mechanical, thermal and chemical stability as compared to other silica-based materials, serve as a useful heterogeneous catalyst system for 1,3-dipolar cycloadditions (“click” reactions) between terminal alkynes and organic azides under green chemistry conditions. The supported CuNPs-CPG catalyst exhibited a broad substrate scope and gave the corresponding triazole products in high yields. The CuNPs-CPG catalyst exhibit recyclability and could be reuced multiple times without contaminating the products with Cu.